Effect of Corporate Governance and Institutional Quality on Firm Performance and Economic Growth in Emerging and Developed Markets: A comparative analysis - Natto, Dinah Milembe (University of the Witwatersrand, Johannesburg, 2024)
Purpose of the study The objective of the current study is to investigate the effects of corporate governance and institutional quality on firm performance and economic growth in emerging and developed markets. These sample countries were selected based on their significant role in their respective economic blocs and based on their unique economic and firm characteristic Research design The impact of corporate governance and institutional quality on firm performance was rigorously evaluated using the Generalized Method of Moments (GMM), while controlling for key variables such as economic growth and other relevant factors. Major findings The study found that corporate governance compliance levels have improved significantly in emerging economies over the study period, with South Africa leading the sample countries. In addition, corporate governance has a significant positive correlation with all firm performance measures in all sample countries. Furthermore, corporate governance has a long-term relationship with ROE and Tobin’s Q in emerging market countries and not in developed countries. However, weak institutions reverse the benefits of a robust corporate governance framework, especially in emerging economies where institutional quality was found to be low. Lastly, the study revealed that over the study period, corporate governance was only found to have a long-term relationship with Tobin’s Qin India. Practical implications Policymakers in emerging and developed markets, the research provides insights into which aspects of corporate governance and institutional quality are most effective in promoting firm performance and economic growth. This can guide the design and implementation of regulations and reforms. Investors can use the findings to assess the risk and potential returns in different markets based on the strength of corporate governance and institutional frameworks. Strong governance and institutions may indicate lower risk and higher stability. Social implication Improved firm performance driven by good governance and strong institutions may lead to better wages and working conditions for employees, reducing income inequality and contributing to social stability. Originality While studies on corporate governance, institutional quality, and their impacts on firm performance and economic growth exist, the originality lies in the comparative analysis between emerging and developed markets. Furthermore, the research integrates the analysis of corporate governance and institutional quality, rather than examining them in isolation.
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Corporate governance; Institutional quality; Firm performance; Economic growth; Emerging Markets; Developed Markets; SDG-8: Decent work and economic growth